2011
DOI: 10.1093/cercor/bhr310
|View full text |Cite
|
Sign up to set email alerts
|

Attention Reverses the Effect of Prediction in Silencing Sensory Signals

Abstract: Predictive coding models suggest that predicted sensory signals are attenuated (silencing of prediction error). These models, though influential, are challenged by the fact that prediction sometimes seems to enhance rather than reduce sensory signals, as in the case of attentional cueing experiments. One possible explanation is that in these experiments, prediction (i.e., stimulus probability) is confounded with attention (i.e., task relevance), which is known to boost rather than reduce sensory signal. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
374
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 376 publications
(438 citation statements)
references
References 57 publications
32
374
10
Order By: Relevance
“…In a study that manipulated the frequency of left/right screen-side presentations of simple visual stimuli, presentation of stimuli on the unexpected side resulted in increased activity in V1 in a condition demanding no attention or evaluation of the stimuli (Kok et al, 2012). In another study where auditory tones predicted presence or absence of visual stimuli (den Ouden et al, 2009), surprising events --either unexpected presentations or omissions of visual stimuli --resulted in increased activity.…”
Section: A Common System For Category and Location Regularitymentioning
confidence: 99%
See 4 more Smart Citations
“…In a study that manipulated the frequency of left/right screen-side presentations of simple visual stimuli, presentation of stimuli on the unexpected side resulted in increased activity in V1 in a condition demanding no attention or evaluation of the stimuli (Kok et al, 2012). In another study where auditory tones predicted presence or absence of visual stimuli (den Ouden et al, 2009), surprising events --either unexpected presentations or omissions of visual stimuli --resulted in increased activity.…”
Section: A Common System For Category and Location Regularitymentioning
confidence: 99%
“…As noted previously (Summerfield & Egner, 2009) differentiating the effects of prediction and attention is quite difficult. However, Kok et al (2012) demonstrated it is possible to differentiate the two by showing that predictable stimuli (in visual cortex) tend to produce less activity when the stream is unattended, but greater activity when the stream is attended to. Thus, whether a certain cortical system shows reduced or increased activity to predictable stimuli (vs. unpredictable) may itself depend on attentional state.…”
Section: Location Regularitiesmentioning
confidence: 99%
See 3 more Smart Citations